Dissolution Behaviour of Laves Phase in P92 High Alloy Steel in Alkaline Solutions. Issue 3 (8th March 2021) - Wu, Yunlong; Yuan, Sui; Yan, Jiayin; Liu, Jiajun; Nong, Jing; Guo, Qi; Xu, Jian
Abstract : The Laves phase precipitates in ASTM A335 P92 (P92) steel were found to dissolve in solutions with NaOH concentration higher than 7 mol l −1 . Such behaviour was utilized to detect and quantify the precipitates in P92 specimens aged at 650 °C for times from 0 to 5000 h. The amount of precipitates was acquired by potentiodynamically polarizing the sample and integrating the dissolution current over time. The result was compared to that of a traditional SEM observation method, and a good linear correlation was found between the results. The dissolution mechanism was discussed based on the electrochemical behaviour of an artificially synthesized Fe2 Mo laves phase specimen, pure Fe, and pure Mo in the strong alkaline solution.